Dietary Intervention with Omega-3 Fatty Acids Mitigates Maternal High-Fat Diet-Induced Behavioral and Myelin-Related Alterations in Adult Offspring - Jastrzębska, Joanna; Frankowska, Małgorzata; Wesołowska, Julita; Filip, Małgorzata; Smaga, Irena (Current Neuropharmacology, 2025)
Background Maternal high-fat diet (HFD) during pregnancy and lactation induces depression-like phenotype and provokes myelin-related changes in rat offspring in the prefrontal cortex (PFCTX), which persist even to adulthood. Objective Due to the plasticity of the developing brain, it was decided to analyze whether depression-like phenotype and myelin-related changes in the early lifetime induced by maternal HFD (60% energy from fat) could be reversed by the omega-3 fatty acid-enriched diet (Ω3D) given from the post-weaning period until adulthood (63rd day of life) in offspring. Methods We analyzed the effect of post-weaning Ω3D on the depressive-like phenotype (assessed by the forced swimming test) and myelin-related changes (measured using RT-qPCR, ELISA, and immunofluorescence staining) in the PFCTX of adult offspring. Results Ω3D reversed increased immobility time in adult offspring induced by maternal HFD, without affecting the animals' locomotor activity. Molecularly, Ω3D normalized the reduced expression levels of myelin-oligodendrocyte glycoprotein (MOG), as well as myelin and lymphocyte protein (MAL) in males and MOG in females in the PFCTX, changes initially induced by maternal HFD. Additionally, Ω3D normalized the quantity of oligodendrocyte precursor cells and mature oligodendrocytes in the prelimbic, infralimbic, and cingulate cortex in males, which were reduced following maternal HFD exposure. In females, the Ω3D effect was less pronounced, with normalization of oligodendrocyte precursors occurring only in the infralimbic cortex. Conclusion These findings suggest that Ω3D may play a significant role in correcting behavioral and neurobiological changes caused by adverse prenatal conditions.
Keywords: high-fat diet